INTEGRASI NILAI-NILAI FILOSOFI TARIAN TOR-TOR SEBAGAI UPAYA PENINGKATAN KEPEDULIAN SOSIAL SISWA SMK - Sabila, Nabia; Isriyah, Mudafiatun; Rahmawati, Weni Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the integration of philosophical values in Tor-Tor dance as an effort to increase the social awareness of vocational high school (SMK) students using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Tor-Tor dance, which is part of Batak culture, contains philosophical values that can be applied in the context of character education and students' social life. The research process began with an analysis of the needs and objectives of program development, followed by the design and development of materials, and implementation in extracurricular activities. Data was collected through observation, interviews with teachers and students, and evaluation of the program that had been implemented. The results of the study showed that the integration of philosophical values in Tor-Tor dance can increase students' social awareness, especially in terms of togetherness, respect, and cooperation. This program also contributes to the formation of students' character who are more concerned about their social environment.